The multifaceted roles of ER and Golgi in metabolic cardiomyopathy - Raja, Rida; Fonseka, Oveena; Ganenthiran, Haresh; Andrea-Ruiz-Velasco,; Liu, Wei (Frontiers in Cardiovascular Medicine, 2022)
Metabolic cardiomyopathy is a significant global financial and health challenge; however, pathophysiological mechanisms governing this entity remain poorly understood. Among the main features of metabolic cardiomyopathy, the changes to cellular lipid metabolism have been studied and targeted for the discovery of novel treatment strategies obtaining contrasting results. The endoplasmic reticulum (ER) and Golgi apparatus (GA) carry out protein modification, sorting, and secretion activities that are more commonly studied from the perspective of protein quality control; however, they also drive the maintenance of lipid homeostasis. In response to metabolic stress, ER and GA regulate the expression of genes involved in cardiac lipid biogenesis and participate in lipid droplet formation and degradation. Due to the varied roles these organelles play, this review will focus on recapitulating the alterations and crosstalk between ER, GA, and lipid metabolism in cardiac metabolic syndrome.